PKM Pengembangan Karya Inovatif Bentuk Alat Peraga untuk Meningkatkan Profesionalisme Kelompok Kerja Guru - Rafiq Badjeber; Wahyuni H Mailili (STKIP Andi Matappa, 2020)
The purpose of this community service activity is in the form of workshops and training to develop innovative works in the form of elementary school teaching aids. The steps for implementing the community partnership program are 1) The stage of preparing and developing training materials; 2) The training phase; 3) The stage of mentoring and practice of KTI 4) The stage of mentoring practice of making teaching aids for elementary school. Service methods used include lecture, discussion and practice methods. The results of the implementation of the service training shows an increase in the ability of teachers in developing knowledge, comprehension, professionalism and creativity in designing teaching aids as a medium for learning mathematics in elementary schools